ENADE: contribuições, avanços, e limites do processo de avaliação dos estudantes de graduação - Viviane Aparecida Rodrigues (2008)
This dissertation is included in the line of research for Public Politic in Education, specifically focusing the evaluations process developed by the Ministry of Education aiming to evaluate the quality of the institutes of higher education. The objective of this study is the analysis of ENADEs contributions for the improvements in the graduations courses which the Universidade Federal de Minas Gerais will be used as reference for the development of proposed searching. Aiming to reach the objective of the proposed study it was previously realized a bibliography research in order to go deeper into the knowledge about the evaluations process introduced into Brazil in the recent period. It was analyzed the evaluating politic in place, that is, SINAES and specifically the ENADE in view of to know their main characteristics. Afterwards it was realized semi-structured interviews with the coordinators and ex- coordinators from the Evaluation Sector called PROGRAD/UFMG due to they are considered main actors in the effective search of improving the background offered by the graduation courses. Among the results from the study it was noticed that the ENADEs introduced new characteristics to the students evaluation process such as application of simultaneous tests for beginners and graduating students, realization of sampling test, tri-annual test etcThose characteristics were introduced aiming to assure that those tests become a diagnostic in the graduation process offered by the college and universities. The realization of interview evidenced that in the first cycle of ENADEs evaluation predominated a distance between Institutions of High Level Education and the debate among of high level educations evaluation process as well as about the testing itself.